Pertumbuhan Tanaman Tomat (Lycopersicon esculentum L.) oleh Cendawan Endofit Akar Mangrove Asal Cagar Alam Pulau Dua Serang Banten (The Growth of Tomato (Lycopersicon esculentum L.) by Endophytic Fungi isolated from Roots of Mangrove Pulau Dua Sanctuary) - Pipit MARIANINGSIH; Rida Oktorida KHASTINI; Deska PURI (Universitas Jambi, 2015)
Tomato (Lycopersicon esculentum L.) is an important horticultural crops but very susceptive in their growth. It is known that the plant growth can be influenced by microorganisms, such as symbiosis between plants and endophytic fungi. Endophytic fungi are fungi that live in the tissues of living plants and will not cause any negative effects on its host. This study aims to determine the growth of tomato plants affected by endophytic fungi isolated from Mangrove root collected from Pulau Dua Sanctuary Serang Banten, both in vitro and in vivo. There were five isolates endophytic fungi of mangrove root (CEM), collection of biology education laboratory UNTIRTA, which is used in this study: CEM 2, CEM 3, CEM 4, CEM 7, and CEM 9. The research conducted by inoculating tomato seedlings on MS medium that has been grown by endophytic fungi for in vitro growth, while the in vivo growth carried out by inoculating tomato seedlings on zeolite medium with corn as a fungi carrier. Morphological observation and plant growth parameters measured after 5 weeks incubation. The result showed that CEM 9 is the potential endophytic fungi from roots of Mangrove Pulau Dua Sanctuary Serang to increase tomato growth.